ALTERNATIF PENYELESAIAN SENGKETA SEBAGAI PERLINDUNGAN HAK ANAK PASCA PERCERAIAN - Muna, Nailal; Anam, Ngurijal; Fatmah (Musawa: Journal for Gender Studies, 2024)
ADR is an out-of-court dispute resolution option pursued by parties to reach a mutually beneficial agreement. It involves negotiation, mediation, coordination and expert judgment. Document No. 0026/Pst.G/PA.Kdr contains cumulative claims that need to be analyzed. This research focuses on the divorce case in the document, identifying the factors behind the post-divorce demands, analyzing the ADR process the plaintiff underwent, and assessing alternative dispute resolution from a women's fiqh perspective. A descriptive qualitative method was used to understand the role of maintenance in the context of these cases, particularly in terms of personal fiqh. The results showed an example of a cumulative lawsuit in Case 0026/Pdt.G/2020/PA.Kdr at the Kediri City Religious Court. The plaintiff filed claims for divorce, child custody and maintenance against the defendant, who is a police officer. These claims were combined because the couple had abandoned the plaintiff and the children for more than two years. The plaintiff chose ADR because she was concerned that the husband would not attend the court hearing. The plaintiff wanted to ensure the children's rights were properly taken care of after the divorce, in line with the principles of women's jurisprudence which views the responsibility of providing for the family as a shared obligation.